Pengaruh Stres Kerja, Komitmen Organisasi, dan Kompensasi terhadap Turnover Intention - Rika Khusnul Khotimah; Anna Partina (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2020)
The turnover intention phenomenon is a threat to the company's operational sustainability. The high turnover rate will affect the cost of recruitment, selection and training. The high level of turnover intention can interfere with the company's operational processes. The purpose of this study was to determine the effect of several variables that could influence turnover intentions, namely job stress, organization and compensation. The sample in this study were permanent employees who worked in the culinary industry, namely SS sambal stalls in Yogyakarta. The sampling technique in this study was saturated samples, where all members of the population were used as samples. The number of samples is 120 employees using multiple linear regression to test the hypothesis. The result of this research is that work stress has a positive and significant effect on turnover intention, organizational commitment has a negative and significant effect on turnover intention, has a negative and insignificant effect on turnover intention.